Promoting physical activity in women survivors of breast cancer - Sequeira, Margarida (2023)
Promoting physical activity (PA) is recommended for women survivors of breast cancer and its benefits and recommendations are identified. However, these women are not active enough, and it is necessary to identify the psychological and social components of an intervention that facilitates behavioral change among these women, towards a more regular practice of PA, that can be used by health professionals, namely physiotherapists. Moreover, the models that explain health behaviors, including PA, have mostly been tested between subjects. In this sense, it was hypothesized that the models that explain health behaviors among groups of individuals can also be explicative and effective in promoting PA behavior among individual survivors of breast cancer, when singular characteristics and individual predisposition for behavioral change towards a regular practice of PA are considered. Hence, one qualitative and two quantitative studies were performed. The first, a qualitative study based on individual interviews, aimed to identify the factors that Portuguese women survivors of breast cancer perceive to influence their regular engagement in PA activities, but also the personal strategies perceived as effective for their regular PA practice, endorsing the selection of some Behavior Change Techniques (BCT). The second, a N-of-1 longitudinal study, aimed to test how the constructs of the Health Action Process Approach (HAPA) model changed over time and how this change predicted PA intentions and daily PA in a group of women survivors of breast cancer. This second study also allowed a deeper analysis of the individual data, aiming to identify whether the pattern of relationships among the more robust constructs of the HAPA model in predicting daily PA, in a group of women survivors of breast cancer, happens in similar or different ways for each of the participants over time. The third study was a N-of-1 Randomized Controlled Trial (RCT), informed by the first ones, that tested the effectiveness of an individual intervention, based on two HAPA constructs/BCT (planning and self-monitoring, the association of both and control conditions), in promoting PA among individual women survivors of breast cancer. The results confirmed that women survivors of breast cancer value different factors according to their particular characteristics, choices, and individual predisposition for behavioral change towards a regular practice of PA. So, the cultural context with some of its idiosyncratic perceived determinants and the identified BCT should be considered by health of PA for breast cancer survivors. Additionally, although study two only partially confirmed the HAPA model at the intrapersonal level, the results obtained provide preliminary evidence that the HAPA can be used at the individual level to understand the specific individual correlates of PA in a population of survivors of breast cancer. Finally, by testing two BCTs, the last study provided a starting point for developing tailored PA interventions for women survivors of breast cancer, revealing that these women do not react the same way to the same active ingredients of an intervention, even when well supported in previous studies and recommendations, since the response to the intervention highlighted intraindividual differences, both in the group and individual analysis performed. Moreover, the identified toolscan enrich physiotherapists’ knowledge and competency for delivering the information and the behavior change interventions, influential for the effectiveness and the adherence to PA recommendations among survivors of breast cancer.